Design of a Clinical CRM Model Integrated with EMR to Support NCD Education - Wijaya, Avid; Soultoni Akbar, Prima; Rohmania Zein, Eiska; Fadly, Fery; Ajeng Trikusumah, Rizka (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2026)
Non-Communicable Diseases (NCDs) have become a major global health issue requiring serious attention, a challenge for the global health system, because of factors such as urbanization, lifestyle changes, and population aging have caused increased cases of diseases such as diabetes, cancer, and cardiovascular disorders worldwide. Clinics play a crucial role in providing health education to the community to increase awareness of NCD prevention. Health service optimization can be achieved through the integration of Customer Relationship Management (CRM) and Electronic Medical Record (EMR) systems, which enable improved patient-provider relationships and more effective access to medical records. This study aims to develop an integrated CRM EMR application model for clinics as a tool for NCD education. The study employed a user-centered design approach with a descriptive research methodology. The research stages consisted of research, requirements, design, and evaluation, conducted through literature reviews, field data collection, and interviews with clinic staff to identify system requirements and user experiences. The design phase produced a database model, relational tables, and a user interface prototype that represent the integration of CRM and EMR systems. The findings indicate that the proposed model has the potential to improve the efficiency of patient data management, facilitate health education, and strengthen interactions between patients and healthcare providers. The main contribution of this research is the provision of technical outputs in the form of a database design and user interface prototype, which can serve as the foundation for further development and implementation of an integrated CRM EMR system in clinics. By embedding the CRM–EMR model within broader e-health strategies and community-based health promotion programs, this research lays the groundwork for a sustainable digital ecosystem that supports preventive healthcare and advances Indonesia’s digital health transformation.